Immunomodulatory effects of regorafenib: Enhancing the efficacy of anti-PD-1/PD-L1 therapy - Liu, Junjie; Tao, Haisu; Yuan, Tong; Li, Jiang; Li, Jian; Liang, Huifang; Huang, Zhiyong; Zhang, Erlei (Frontiers in Immunology, 2022)
Anti-PD-1/PD-L1 therapy has shown significant benefits in the treatment of a variety of malignancies. However, not all cancer patients can benefit from this strategy due to drug resistance. Therefore, there is an urgent need for methods that can effectively improve the efficacy of anti-PD-1/PD-L1 therapy. Combining anti-PD-1/PD-L1 therapy with regorafenib has been demonstrated as an effective method to enhance its therapeutic effect in several clinical studies. In this review, we describe common mechanisms of resistance to anti-PD-1/PD-L1 therapy, including lack of tumor immunogenicity, T cell dysfunction, and abnormal expression of PD-L1. Then, we illustrate the role of regorafenib in modifying the tumor microenvironment (TME) from multiple aspects, which is different from other tyrosine kinase inhibitors. Regorafenib not only has immunomodulatory effects on various immune cells, but also can regulate PD-L1 and MHC-I on tumor cells and promote normalization of abnormal blood vessels. Therefore, studies on the synergetic mechanism of the combination therapy may usher in a new era for cancer treatment and help us identify the most appropriate individuals for more precise treatment.